Machinations from on High: U.S. Aid Plan and Oil in South Korea*. - Kwon, Ohsoo (Diplomatic History, 2022)
The contracts would be signed between the South Korean government, the U.S. government, and the oil companies, allowing the Three Sisters to handle petroleum products by the GARIOA funds under the control of the South Korean government. Particularly problematic during the Initial Settlement process was Article 9, Clause C (2), which pertained to "the acquisition of property located in Korea, ... including improvements to any property in which the Government of the United States of America has an interest."[43] In fact, the South Korean government did not oppose the U.S. government's acquisition of Korean property. On December 21 and 22, 1948, the U.S. government and the Three Sisters held a meeting with the South Korean government, but the two negotiating bodies did not comment on the Lease Agreement.[69] Finally, on January 4, 1949, the South Korean government, the U.S. government, and the KOSCO signed the Operating Agreement and nothing else. After World War II, the United States government took control of world oil, a maneuver that not only reflected a convergence of interests between the U.S. government and American oil companies but also brought to bear close and permanent ties with oil companies around the world.